2014
DOI: 10.1021/jp506983s
|View full text |Cite
|
Sign up to set email alerts
|

Incisive Probing of Intermolecular Interactions in Molecular Crystals: Core Level Spectroscopy Combined with Density Functional Theory

Abstract: The α-form of crystalline para-aminobenzoic acid (PABA) has been examined as a model system for demonstrating how the core level spectroscopies X-ray photoelectron spectroscopy (XPS) and near-edge X-ray absorption fine-structure (NEXAFS) can be combined with CASTEP density functional theory (DFT) to provide reliable modeling of intermolecular bonding in organic molecular crystals. Through its dependence on unoccupied valence states NEXAFS is an extremely sensitive probe of variations in intermolecular bonding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 68 publications
4
33
0
Order By: Relevance
“…Furthermore,t he obvious decrease in intensity was caused by the p* orbital in the NiN 4 structure being filled with electrons from the CNTs.T he broad peak at 406.1 eV in Ni-TAPc originated from the 1s-s* transitions of N À H, which was attributed to amino N. Thed isappearance of this peak in Ni-CNT-CC indicated that amino Nh ad been consumed, in accordance with the synthesis method. [13] Meanwhile,F igure 1f showed an approximate 0.6 eV shift (from 35.2 to 35.8 eV) in the second electron cutoff edge to ah igher binding energy after attaching Ni-TAPc to CNTs.This indicated ad ecrease in the work function (from 4.8 to 4.2 eV), which suggested that electrons flowed to the NiN 4 structure after Ni-CNT-CC formation, in agreement with the results of NKedge analysis. [14] TheCO 2 RR activity of the model Ni SACwas evaluated on ar otating disk electrode (RDE) in 0.5 m KHCO 3 electrolyte using linear sweep voltammetry (LSV; Figure 2a).…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore,t he obvious decrease in intensity was caused by the p* orbital in the NiN 4 structure being filled with electrons from the CNTs.T he broad peak at 406.1 eV in Ni-TAPc originated from the 1s-s* transitions of N À H, which was attributed to amino N. Thed isappearance of this peak in Ni-CNT-CC indicated that amino Nh ad been consumed, in accordance with the synthesis method. [13] Meanwhile,F igure 1f showed an approximate 0.6 eV shift (from 35.2 to 35.8 eV) in the second electron cutoff edge to ah igher binding energy after attaching Ni-TAPc to CNTs.This indicated ad ecrease in the work function (from 4.8 to 4.2 eV), which suggested that electrons flowed to the NiN 4 structure after Ni-CNT-CC formation, in agreement with the results of NKedge analysis. [14] TheCO 2 RR activity of the model Ni SACwas evaluated on ar otating disk electrode (RDE) in 0.5 m KHCO 3 electrolyte using linear sweep voltammetry (LSV; Figure 2a).…”
Section: Resultsmentioning
confidence: 96%
“…[20,21] Such a low-lying energy feature is, therefore, completely absent in small metal-free N-containing molecules. [12,22,23] The metal-free porphyrin (2HTPP) usually has the first N absorption feature located more than 1 eV below the metal-N peak with much reduced intensity, arising from the inequivalence of the N species in the absence of the metal centre, leading to iminic =N− and pyrrolic −NH− nitrogen. [20,21] The slight energy shift between the two absorption edges at around 398 eV is made evident by the blue-highlighted area in the difference plot, which actually indicates a broadening, instead of an energy shift, of the first absorption feature for the hemin dimer species since its peak position at 398.5 eV does not exhibit observable shift when compared with that of hemin monomer (the broadening effect is discussed below).…”
Section: Resultsmentioning
confidence: 99%
“…The absorption features at 400-403 eV (green-highlighted) originate from N * orbitals as N is part of the aromatic ring system, while the arising absorption edges at the brown-highlighted area are in the region of the ionization potentials (IPs). [12,22] The N * orbitals and IP thus exhibit distinguishable characteristics for different hemin solutions. The exact origins of these differences will be discussed in detail for Figure 3 below.…”
Section: Resultsmentioning
confidence: 99%
“…Although core hole relaxation effects are expected to affect the energetic position of features in the NEXAFS and RIXS data, the impact on taking the experimental RIXS-NEXAFS energy gap as a measure of the HOMO-LUMO is believed to be of the order of at most a few 100 meV; additionally, when such effects were included in CASTEP calculations for crystalline PABA [5] the inclusion of final-state effects did not change the MO interpretation significantly. For the DFT calculations, omitting relaxation effects may lead to a slight overestimation of transition energies, and thus of the RIXS-NEXAFS energy gap.…”
Section: Resultsmentioning
confidence: 99%